Chemical profiling and antioxidant studies on the leaf of Breonadia salicina Hepper and J. R. I. Wood (Rubiaceae) - Ismaila, Sani (Polish Journal of Natural Sciences, 2023)
This study evaluated the antioxidant properties of the leaves of Breonardia salicina and the profiling of its chemicals. Ethno medically, the leaves of the plant are widely used the for treatment of cancer, gastrointestinal diseases, fevers, headaches, arthritis, diabetes, inflamed wounds, and ulcers. The plant is an evergreen growing along riverbanks, streams, and river tributaries, belonging to the family Rubiaceae. Collection and identification of the plant, extracts,and fractionation of the sample collected, then antioxidant evaluation using DPPH and ABTS methods and, finally chemical profiling of the sample using LC-ESI-MS/MS. Antioxidant equivalence of the leaf extracts/fractions of the plant at R2 value of 0.9938 and standard equation (y = 0.9891x - 1.996) was found to be highest at 281.7 ± 0.8mg Trolox Equivalent and lowest at 118.7 ± 2.7 mg Trolox Equivalent. The LC-ESI-MS/MS of the sample identified 22 compounds with their structures, belonging to different classes including flavonoids, glycosides, phenolic acids, triterpenoids, amides, and sulphonamides. The identified compounds are of medicinal importance, which is undoubtedly responsible for the antioxidant and anticancer properties of the plant. The good antioxidant values obtained revealed the possible use of the plant in the treatment of many diseases that are known to respond to antioxidation.